Diaspora Effects in International Migration Key Questions and Methodological Issues - Beine, Michel (The World Bank, 2011)
This paper reviews the existing literature on the impact of migrants networks on the patterns of international migration. It covers the theoretical channels at stake in the global effect of the networks. It identifies the key issues, namely the impact on size, selection and concentration of the migration flows. The paper also reviews the empirical hurdles that the researchers face in assessing the importance of networks. The key issues concern the choice of micro vs a macro approach, the definition of a network, the access to suitable data and the adoption of econometric methods accounting for the main features of those data. Finally, the paper reports a set of estimation outcomes reflecting the main findings of the macro approach